“Success is in your hand”: Digital literacy to support students’ autonomous learning in speaking class - Saraswati, Girindra Putri Dewi; Areni, Galuh Kirana Dwi; Anellysha, Destya (ELT Forum: Journal of English Language Teaching, 2021)
The expected objectives of the results of this study are to obtain a concrete picture of students' digital literacy mastery in the Transactional Conversation course and to find out the effect of students' digital literacy mastery on the quality of autonomous learning in the Transactional Conversation course. In particular, this study will examine theories on digital literacy and autonomous learning in the Transactional Conversation course. The approach to be applied in this research is interdisciplinary using qualitative methods. The research design used is a case study. The technique of collecting data uses participatory observation techniques, interviews, and document studies. The data validity technique used triangulation, which mainly consisted of source data triangulation, methodological triangulation, and theory triangulation. The results show that there is a relationship between digital literacy mastery and the quality of autonomous learning. The role of the lecturer as a facilitator invites students to have the courage to evaluate the quality of their own learning.